Handbook of research on strategic supply chain management in the retail industry - Kamath, Narasimha; Saurav, Swapnil; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book is an authoritative reference source for the latest scholarly research on properly managing business processes in order to satisfy end-user requirements and increase competitive advantage in the retail marketplace"--Provided by publisher.
End to end supply chain planning for a fashion retailer in India / Aravind D. -- Intelligent slotting for the warehouse / Narayanan Padmanabahan Iyer, Ramesh Jayal -- A study of virtual trial room / Safa Albadri -- Retail healthcare market in India: readiness of consumers and physicians to accept new industry structure - on call at the mall / Rupali Das.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 02/20/2016).
Keywords: Retail trade; Business logistics; Big data analytics; Green retailing; Intelligent warehouse slotting; Multi-retailer systems; Omni-channel retailing; Perishable goods; Safety stock; Electronic books